2017
DOI: 10.1002/ece3.3471
|View full text |Cite
|
Sign up to set email alerts
|

Detecting latitudinal and altitudinal expansion of invasive bamboo Phyllostachys edulis and Phyllostachys bambusoides (Poaceae) in Japan to project potential habitats under 1.5°C–4.0°C global warming

Abstract: Rapid expansion of exotic bamboos has lowered species diversity in Japan's ecosystems by hampering native plant growth. The invasive potential of bamboo, facilitated by global warming, may also affect other countries with developing bamboo industries. We examined past (1975–1980) and recent (2012) distributions of major exotic bamboos (Phyllostachys edulis and P. bambusoides) in areas adjacent to 145 weather stations in central and northern Japan. Bamboo stands have been established at 17 sites along the latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…henonis, which are called the three major useful bamboos in Japan [34,41]. In Japan, bamboo forests are estimated to cover more than 150,000 ha [42,43]; these three species account for more than 99% [44]. Hence, developing allometric equations is helpful to evaluating the potential of the bamboo forests as a carbon sink.…”
Section: Introductionmentioning
confidence: 99%
“…henonis, which are called the three major useful bamboos in Japan [34,41]. In Japan, bamboo forests are estimated to cover more than 150,000 ha [42,43]; these three species account for more than 99% [44]. Hence, developing allometric equations is helpful to evaluating the potential of the bamboo forests as a carbon sink.…”
Section: Introductionmentioning
confidence: 99%
“…These habitats are probably not yet all colonised because minimal temperatures may be too low. Recent studies found invasive Poaceae species like Botriochloa ischaemum (L.) Keng , Anisantha tectorum (L.) Nevski or bamboo species to be favoured by warmer and wetter environments (Shi et al ., ; Blumenthal et al ., ; Takano et al ., ). This trend has also been forecast with modelling approaches (Bradley, ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, bamboo expansion has become an important problem in Japan because of its invasiveness [ 18 ]. Although some studies have analyzed the bamboo forest distribution probability on a national scale [ 26 , 27 ], monitoring of bamboo expansion is still challenging because it is labor-intensive. Nonetheless, our method has a certain degree of robustness in reducing the amount of training data (see Fig.…”
Section: Discussionmentioning
confidence: 99%